Efficacy of powdered maize cobs against the maize weevil Sitophilus zeamais (Coleoptera: Curculionidae) in stored maize in Senegal - Gueye, M.T.; Cissokho, P.S.; Goergen, Georg E.; Ndiaye, S.; Seck, D.; Gueye, G.; Wathelet, J.P.; Lognay, G. (Springer, 2012)
Powdered maize cobs were tested as an alternative for pesticide use in stored maize. Five doses (2, 4, 6, 8 and 10 g/250 g seed) of powdered maize cobs applied at particle sizes of 1.4 and 0.4mm diameter were compared with actellic powder against Sitophilus zeamais Motschulsky for 120 days. Mortality and survival data showed that cob powders did not act as fumigant but exerted a potent inhibition of progeny on direct contact with S. zeamais adults. The particle size of powdered cobs had no effect on maize damage and losses. At doses equal to or higher than 6 g powdered maize cobs/250 g grain maize, i.e. 2.4% (w/w), damage to grain was ,5% and weight losses ,1%. The protection offered at the highest dose was comparable to the pesticide control. The use of powdered maize cobs is discussed as a natural alternative to synthetic pesticides for protection of maize against S. zeamais.